Expresión ¬(x)zvxyzv¬xz
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(z∧¬x)∨(x∧y∧z)=z∧(y∨¬x)
z∧(y∨¬x)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
(y∧z)∨(z∧¬x)
Ya está reducido a FNC
z∧(y∨¬x)
(y∧z)∨(z∧¬x)
z∧(y∨¬x)